2022
DOI: 10.1038/s41419-022-04585-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cell apoptosis modulates the colorectal cancer immune microenvironment via interleukin-8-dependent neutrophil recruitment

Abstract: Sporadic apoptosis of tumour cells is a commonly observed feature of colorectal cancer (CRC) and strongly correlates with adverse patient prognosis. The uptake of apoptotic cell debris by neutrophils induces a non-inflammatory, pro-regenerative, and hence potentially pro-tumorigenic phenotype. In this study, we therefore sought to investigate the impact of apoptotic CRC cells on neutrophils and its consequence on other immune cells of the tumour microenvironment. Apoptosis induced by combined TNFα-treatment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…As shown in Figure 1 D, PMA treatment of PBMCsec pre-incubated neutrophils led to a comparable inhibition of DNA release. Additionally, we evaluated the metabolic activity of ionomycin-activated neutrophils [ 41 ]. Ionomycin-activation resulted in a prominent decrease in metabolic activity which, in contrast to vehicle treatment, was completely abolished by the addition of PBMCsec ( Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 D, PMA treatment of PBMCsec pre-incubated neutrophils led to a comparable inhibition of DNA release. Additionally, we evaluated the metabolic activity of ionomycin-activated neutrophils [ 41 ]. Ionomycin-activation resulted in a prominent decrease in metabolic activity which, in contrast to vehicle treatment, was completely abolished by the addition of PBMCsec ( Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in figure 1D, PMA treatment of PBMCsec pre-incubated neutrophils led to a comparable inhibition of DNA release. Additionally, we evaluated the metabolic activity of ionomycin-activated neutrophils (52). Ionomycin-activation resulted in a prominent decrease of metabolic activity which in contrast to vehicle treatment, was completely abolished by the addition of PBMCsec (Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Giving importance to the neutrophil-induced M2-like macrophage phenotype, the blocking of the neutrophil accumulation in the TME represents a promising therapeutic approach to hinder neutrophil-mediated immune suppression. In this line, the latest study has shown that the blocking of CXCL-8 signaling suppresses neutrophil migration and the neutrophil-mediated polarization of anti-inflammatory macrophages in the TME ( 247 ). The above discussed findings support that CXCL8 plasma levels can provide a glimpse into the immunosuppressive TME and patients may benefit from immune checkpoint blockade therapy, following the reduction of the CXCL8 level.…”
Section: Strategies To Target Neutrophilsmentioning
confidence: 99%